An Improved Micropropagation Protocol by Ex Vitro Rooting of Passiflora edulis Sims. f. flavicarpa Deg. through Nodal Segment Culture - Mahipal S. Shekhawat; M. Manokari; C. P. Ravindran (Scientifica)
A procedure for rapid clonal propagation of Passiflora edulis Sims. f. flavicarpa Deg. (Passifloraceae) has been developed in this study. Nodal explants were sterilized with 0.1% HgCl2 and inoculated on Murashige and Skoog (MS) basal medium. The addition of 2.0 mgL−1 6-benzylaminopurine (BAP) to MS medium caused an extensive proliferation of multiple shoots (8.21±1.13) primordial from the nodal meristems. Subculturing of these multiple shoots on the MS medium augmented with 1.0 mgL−1 of each BAP and Kinetin (Kin) was successful for the multiplication of the shoots in vitro with maximum numbers of shoots (25.73±0.06) within four weeks of incubation. Shoots were rooted best (7.13±0.56 roots/shoots) on half strength MS medium supplemented with 2.0 mgL−1 indole-3 butyric acid (IBA). All in vitro regenerated shoots were rooted by ex vitro method, and this has achieved 6-7 roots per shoot by pulsing of cut ends of the shoots using 200 as well as 300 mgL−1 IBA. The plantlets were hardened in the greenhouse for 4-5 weeks. The hardened plantlets were shifted to manure containing nursery polybags after five weeks and then transferred to a sand bed for another four weeks for acclimatization before field planting with 88% survival rate.